Designing Entrustable Professional Activities for Treatment Planning of Oral Cancer by Maxillofacial Surgery Residents: A Modified Delphi Study - Maidah Hanif; Yawar Hayat Khan; Kamran Ali (International Journal of Dentistry)
Purpose. The aim of this study was to develop a competency framework based on entrustable professional activities (EPAs) in oral cancer management by postgraduate trainees in oral and maxillofacial surgery through expert consensus. Materials and Methods. The study design was based on a modified Delphi technique and involved iterative online surveys with two rounds of data collection and analysis. Initial development of the questionnaire identified five EPAs based on 42 competencies along with supervision level and assessment strategies. The first Delphi round involved administration of the survey questionnaire online to maxillofacial surgeons meeting the inclusion criteria for experts. Consensus was achieved on five EPAs and 36 competencies (≥80% response rate). Six competencies were rephrased and sent again in the Round 2 questionnaire to achieve a consensus. Results. A total of 45 experts participated in Round 1 followed by input from 27 experts in Round 2 of the Delphi panel. Following two iterative rounds of online surveys and feedback, expert consensus was achieved to develop an EPA framework in five EPA domains focused on the management of oral cancer by postgraduate trainees in maxillofacial surgery including 38 specific competencies, supervision level, and assessment strategies. High content validity of the study was established through a comprehensive literature search, and expert feedback was evidenced by an excellent response rate (93.34%, and 64.28%) and a stringent criteria of response agreement amongst experts (≥80%). Conclusion. In conclusion, this study employed expert consensus to identify five EPAs with 38 competencies along with the required supervision level of postgraduate maxillofacial trainees for the management of oral cancer. This EPA framework provides a roadmap for training supervisors to map the learning outcomes in oral oncology for postgraduate trainees in oral and maxillofacial surgery.